THE ORGANIZATION OF STUDENTS' SELF-STUDY IN PIANO CLASS FOR VARIABLE PROFESSIONAL ACTIVITIES - Veronika S. Korina (Moscow Polytechnic University, 2017)
The article addresses the issues concerning the improvement of musician-pedagogues' professional training at higher educational institution. The article presents the example of modeling and organizing the self-study in the piano class. The author substantiates the necessity to revise the traditional approaches to self-study organizing, emphasizes the importance of forming mental abilities, memory and thinking, reveals the content of the concept "musician-pedagogue's professional self-study in piano class", identifies the key areas of students' self-study according to theoretical disciplines and courses of the curriculum. As a result the key elements of professional training of a musician-pedagogue in piano class are determined.